Conductive adhesive for target material and preparation method thereof
Through the medium-temperature curing technology of two-component conductive adhesive, phenyl hydrogen-containing silicone oil containing silicone bonds at the end side is used as a curing agent to solve the problem of target cracking during high-temperature curing of existing conductive adhesives, and achieve medium-temperature curing bonding, with excellent conductivity and low-temperature resistance.
Patent Information
- Application Number
- CN202411893310.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-04
AI Technical Summary
The existing conductive adhesives are prone to cracking the target material when cured at high temperature, and the high temperature recovery of the thermally cured conductive adhesives leads to increased stress, making it difficult to meet the needs of medium-temperature curing bonding of the target material.
Two-component conductive glue is used, and components A and B contain phenyl vinyl silicone oil, conductive fillers and other components, respectively. The phenyl hydrogen-containing silicone oil containing silicone bonds at the end is used as the curing agent, and the medium-temperature curing bond of the conductive glue is achieved through medium-temperature curing (60℃~80℃) mixing and curing.
After curing at 80°C, the conductive glue has good tensile strength, elongation of break, shear strength and other properties. It does not require heating to high temperatures above 100°C. It has excellent conductivity and good low temperature resistance, and can maintain elasticity to about minus 70°C.
Smart Images

Figure BDA0005201134650000021 
Figure BDA0005201134650000022 
Figure BDA0005201134650000023
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive adhesives, and in particular to a conductive adhesive for target materials and a preparation method thereof. Background Art
[0002] Metal sputtering target technology is widely used in the semiconductor industry. With the rapid development of the electronics industry, the demand for target materials has also become diverse, and its structural form has also changed from the traditional plane to the curved surface. Such changes have brought new challenges to the manufacture of target materials. The target material is mainly composed of sputtering material, target or backing material and connecting material. The backing material is mainly various metals, such as stainless steel, and the sputtering material is mainly composed of various metals or non-metals. The connecting material is mainly tin, which plays the role of conductive bonding and fixing. Tin has excellent conductivity and stable bonding, but when the curved target material is designed, such as silicon target and stainless steel substrate, because silicon is relatively brittle, and the expansion coefficients of silicon and stainless steel are different in the curved surface, the hardness of tin is relatively large. This connection method can easily cause the silicon target to break due to stress, so an elastic conductive material is needed to solve such problems.
[0003] At present, the elastic conductive material on the market is mainly silicone conductive adhesive, and the condensation type conductive adhesive is mainly used, which relies on the moisture in the air to solidify. However, due to the large bonding area of the target material, the middle part cannot be penetrated by air, which will cause the middle part to not solidify. Another type of heat-curing addition conductive adhesive is cured by heating reaction, usually at a heating temperature above 100°C, but the stress generated when the high temperature is restored to a low temperature is more likely to cause cracking of the silicon material. Therefore, how to develop a conductive adhesive that can be cured and bonded at medium temperature (60°C to 80°C) to meet the application needs of the target material is a technical problem that needs to be solved urgently. Summary of the invention
[0004] In view of the above problems, the present invention provides a conductive adhesive for target material and a preparation method thereof.
[0005] In one aspect, the present invention provides a conductive adhesive for a target material, wherein the conductive adhesive for a target material comprises a component A and a component B; wherein:
[0006] In parts by mass, component A comprises:
[0007] 100 parts of phenyl vinyl silicone oil,
[0008]
[0009] In parts by mass, component B comprises:
[0010]
[0011] Wherein, the curing agent is selected from phenyl hydrogen-containing silicone oil containing silicon-hydrogen bonds at the terminal side.
[0012] Optionally, the structure of the tackifier is as follows:
[0013]
[0014] Among them, a≥4, b≥5, c≥4, d≥3, e≥3.
[0015] Optionally, the phenyl vinyl silicone oil is one or more selected from phenyl vinyl silicone oils having a vinyl content of 0.16 to 0.57% and a phenyl content of 2 to 8%.
[0016] Optionally, the curing agent is one or more selected from phenyl hydrogen-containing silicone oils having a terminal silicon-hydrogen bond content of 0.1 to 0.8% and a phenyl content of 2 to 8%.
[0017] Optionally, the inhibitor is one or more selected from acetylenic alcohols, ether compounds, amine compounds, vinyl ring compounds, and fumarate compounds.
[0018] Optionally, the diluent is selected from α,ω-dimethyl polydimethylphenylsiloxane having a viscosity of 10 to 100 mPa.s and a phenyl content of 2 to 8%.
[0019] Optionally, the conductive filler is one or more spherical silver-coated copper powders and / or silver-coated aluminum powders with different particle sizes.
[0020] Optionally, the particle size of the conductive filler is 20-50 μm.
[0021] Optionally, the catalyst is a platinum catalyst.
[0022] On the other hand, the present invention also provides a method for preparing a conductive adhesive for a target material, comprising:
[0023] (1) Mix the following components by weight and degas:
[0024]
[0025] Then, it is mixed with 400 to 650 parts of conductive filler and degassed to obtain component A;
[0026] Wherein, the curing agent is selected from phenyl hydrogen-containing silicone oil containing silicon-hydrogen bonds at the end side;
[0027] (2) Mix and degas the following components in parts by mass:
[0028] 100 parts of phenyl vinyl silicone oil,
[0029] 0.1 to 0.8 parts of catalyst,
[0030] 4 to 8 parts of diluent;
[0031] Then, the mixture is mixed with 400 to 650 parts of a conductive filler and degassed to obtain a B component.
[0032] Beneficial effects:
[0033] (1) The conductive adhesive of the present invention has good tensile strength, elongation at break, shear strength, etc. after being cured at 80°C, and does not need to be heated to a high temperature above 100°C. It can achieve medium-temperature curing and bonding, and has excellent conductive properties;
[0034] (2) The conductive adhesive of the present invention has good low temperature resistance and can maintain good elasticity to about -70°C, thus solving the problem of easy cracking when tin welding is used to bond brittle target materials;
[0035] (3) The present invention uses a tackifier with a specific structure to further improve the conductive properties, tensile strength, elongation at break, shear strength and other properties of the conductive adhesive, thereby obtaining a conductive adhesive with better comprehensive properties. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below through examples. Through these examples, the features and advantages of the present invention will become clearer and more specific.
[0037] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.
[0038] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0039] In one aspect, the present invention provides a conductive adhesive for a target material, wherein the conductive adhesive for a target material comprises a component A and a component B; wherein:
[0040] In parts by mass, component A comprises:
[0041]
[0042] In parts by mass, component B comprises:
[0043]
[0044] Wherein, the curing agent is selected from phenyl hydrogen-containing silicone oil containing silicon-hydrogen bonds at the terminal side.
[0045] First, a single-component adhesive may mean that all components have been pre-mixed together and can be used directly, while a two-component adhesive may include two independent components, such as component A and component B, and component A and component B may respectively contain many specific components, and component A and component B need to be mixed before use. When the conductive adhesive for target material of the present invention is used, component A and component B can be mixed in a mass ratio of 1:1, and a conductive adhesive with excellent low temperature resistance can be obtained after medium temperature curing.
[0046] Secondly, silicone oil usually refers to linear polysiloxane products that remain liquid at room temperature, which are generally divided into two categories: methyl silicone oil and modified silicone oil. The most commonly used silicone oil is methyl silicone oil, also known as ordinary silicone oil, whose organic groups are all methyl, and its structure can be shown as Methyl silicone oil has good chemical stability, insulation, and good hydrophobic properties. Phenyl vinyl silicone oil refers to silicone oil containing phenyl and vinyl. Phenyl hydrogen silicone oil refers to silicone oil containing phenyl and silicon-hydrogen bonds. Phenyl hydrogen silicone oil with silicon-hydrogen bonds at the end side refers to phenyl hydrogen silicone oil with silicon-hydrogen bonds at both the end and side positions. The structure of phenyl hydrogen silicone oil with silicon-hydrogen bonds at the end side can be schematically shown but not limited to the following structure:
[0047]
[0048] After long-term research and development experiments, the inventors of the present application found that phenyl hydrogen-containing silicone oil containing silicon-hydrogen bonds on the end side is used as a curing agent, and is compounded with phenyl vinyl silicone oil, inhibitor, diluent, tackifier, and conductive filler according to the above-mentioned mass ratio to form component A. At the same time, phenyl vinyl silicone oil is compounded with catalyst, diluent, and conductive filler according to the above-mentioned mass ratio to form component B. In this way, the specific components contained in components A and B are mixed only when used. Phenyl hydrogen-containing silicone oil containing silicon-hydrogen bonds on the end side can not only better play a curing role, but also has good elasticity after curing, and has good tensile strength, elongation at break, shear strength, etc. The various components in the conductive adhesive can play a very good synergistic role. The conductive adhesive does not need to be heated to a high temperature of more than 100°C, and can be well cured at only 80°C, realizing medium-temperature curing and bonding. At the same time, it can also have excellent conductive properties, etc., with excellent comprehensive performance. In addition, the conductive adhesive also has good low-temperature resistance, and can still maintain good elasticity even when the temperature drops to minus 70°C. Research has found that if the components with the same ratio as above are used in a single-component form, the components will come into contact too early and cannot be stored. The two-component form of AB components makes the medium-temperature curing conductive adhesive with excellent performance easy to use.
[0049] In one embodiment of the conductive adhesive for target material of the present invention, the structure of the tackifier is as follows:
[0050]
[0051] Among them, a≥4, b≥5, c≥4, d≥3, e≥3.
[0052] It should be noted that after years of research and development experiments, the inventors of the present application unexpectedly discovered that using polydimethylphenylsiloxane containing phenyl, alkoxy, acyloxy and silicon-hydrogen bonds and having the structural formula shown above as a thickener, the thickener with the above structure can not only better play a thickening role, but also the various components in the conductive adhesive can better synergize and enhance the effectiveness. The conductive adhesive can be well cured at a lower temperature, and the tensile strength, elongation at break, shear strength, etc. are further improved. It can better achieve medium-temperature curing and bonding, and various properties such as low-temperature resistance and conductivity are further greatly improved, resulting in a conductive adhesive with better comprehensive performance.
[0053] In addition, the preparation method of the above structural tackifier may include:
[0054] Take 30-50g of octaphenylcyclotetrasiloxane D 4 Ph, 160-185g octamethylcyclotetrasiloxane, 22-34g tetramethylhydrogencyclotetrasiloxane D 4 H, 3-7g hexamethyldisiloxane, add 15-25g of 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually raise the temperature to 230°C, and stop the reaction when there is no distillate. Take 150-180g of the transparent polymer in the bottle, place it in a 500ml three-necked flask, add 30-350ml of toluene solvent, add 3-4g of 2000ppm isopropanol solution of chloroplatinic acid, control the reaction temperature between 30-60°C through an oil bath, add 40-45g of 3-(methacryloyloxy)propyltrimethoxysilane drop by drop, and continue to add 27-35g of vinyltrimethylsiloxane drop by drop after adding, maintain the above temperature, react for 4h, distill the product after the reaction, remove the low-boiling substances, and obtain the above transparent tackifier.
[0055] In another embodiment of the aforementioned conductive adhesive for target materials of the present invention, the phenyl vinyl silicone oil is one or more selected from phenyl vinyl silicone oils having a vinyl content of 0.16 to 0.57% and a phenyl content of 2 to 8%.
[0056] It should be noted that the phenyl vinyl silicone oil in component A and component B may be the same or different, and may be selected from the above-mentioned phenyl vinyl silicone oil. In the conductive adhesive for target material of the present invention, the phenyl vinyl silicone oil with a vinyl content of 0.16-0.57% and a phenyl content of 2-8% is compounded with other components, and the conductive adhesive after mixing component A and component B can obtain better performance.
[0057] In addition, the aforementioned phenyl vinyl silicone oil can be synthesized as follows:
[0058] Take 15-64g of octaphenylcyclotetrasiloxane D4 Ph, 200-340g octamethylcyclotetrasiloxane, 4-20g tetramethyldivinylsiloxane, add 10-20g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually raise the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer, which is the aforementioned phenyl vinyl silicone oil.
[0059] In another embodiment of the conductive adhesive for target materials of the present invention, the curing agent is one or more selected from phenyl hydrogen-containing silicone oils having a terminal silicon-hydrogen bond content of 0.1 to 0.8% and a phenyl content of 2 to 8%.
[0060] It should be noted that the terminal silicon-hydrogen bond content represents the total content of terminal and side silicon-hydrogen bonds. Phenyl hydrogen-containing silicone oil with a terminal silicon-hydrogen bond content of 0.1-0.8% and a phenyl content of 2-8% is used as a curing agent and is compounded with other components according to the above-mentioned mass ratio. The components can better synergize and enhance each other to further improve the performance of the conductive adhesive.
[0061] In addition, the phenyl hydrogen-containing silicone oil containing a silicon-hydrogen bond at the terminal side of the aforementioned curing agent can be synthesized as follows:
[0062] Take 15-100g of octaphenylcyclotetrasiloxane D 4 Ph, 200-340g octamethylcyclotetrasiloxane, 30-60g tetramethylhydrogencyclotetrasiloxane D 4 H, 3-9g tetramethyldihydrogensiloxane, add 10-20g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually raise the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer, which is the aforementioned phenyl hydrogen-containing silicone oil containing silicon-hydrogen bonds on the end side.
[0063] In one embodiment of the aforementioned conductive adhesive for target materials of the present invention, the inhibitor is one or more selected from acetylenic alcohols, ether compounds, amine compounds, vinyl ring compounds, and fumarate compounds.
[0064] It should be noted that a conductive agent with excellent performance can be obtained by compounding the above-mentioned type of inhibitor with the aforementioned other components.
[0065] In another embodiment of the aforementioned conductive adhesive for target materials of the present invention, the diluent is selected from α,ω-dimethyl polydimethylphenylsiloxane having a viscosity of 10 to 100 mPa.s and a phenyl content of 2 to 8%.
[0066] It should be noted that the diluents in component A and component B may be the same or different, and may be selected from the above-mentioned α,ω-dimethyl polydimethylphenyl siloxane. α,ω-dimethyl polydimethylphenyl siloxane with a viscosity of 10 to 100 mPa.s and a phenyl content of 2 to 8% is used as a diluent, and other components are combined according to the above-mentioned mass ratio to form component A and component B, and the resulting conductive adhesive has excellent properties.
[0067] In addition, the aforementioned α,ω-dimethyl polydimethylphenylsiloxane as a diluent can be synthesized as follows:
[0068] Take 15-64g of octaphenylcyclotetrasiloxane D 4 Ph, 200-340g octamethylcyclotetrasiloxane, 30-50g tetramethylcyclotetrasiloxane, 3-9g hexamethyldisiloxane, add 10-20g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually raise the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer, which is the aforementioned diluent α, ω-dimethyl polydimethylphenylsiloxane.
[0069] In one embodiment of the aforementioned conductive adhesive for target materials of the present invention, the conductive filler is one or more spherical silver-coated copper powders and / or silver-coated aluminum powders with different particle sizes.
[0070] It should be noted that the conductive fillers in component A and component B may be the same or different, and may be selected from the above-mentioned spherical silver-coated copper powder and / or silver-coated aluminum powder.
[0071] In one embodiment of the aforementioned conductive paste for target materials of the present invention, the particle size of the conductive filler is 20 to 50 μm.
[0072] It should be noted that the particle sizes of the conductive fillers in component A and component B can be the same or different, and can be 20 to 50 μm respectively. Selecting the above conductive fillers and controlling the particle sizes of the conductive fillers as above can not only improve the conductive properties of the conductive adhesive, but also help improve the overall properties of the conductive adhesive.
[0073] In one embodiment of the aforementioned conductive adhesive for target materials of the present invention, the catalyst is a platinum catalyst.
[0074] It should be noted that the platinum catalyst is compounded with phenyl vinyl silicone oil, diluent and conductive filler to form component B, and at this time the conductive adhesive can have excellent performance.
[0075] On the other hand, the present invention also provides a method for preparing a conductive adhesive for a target material, comprising:
[0076] (1) Mix the following components by weight and degas:
[0077]
[0078] Then, it is mixed with 400 to 650 parts of conductive filler and degassed to obtain component A;
[0079] Wherein, the curing agent is selected from phenyl hydrogen-containing silicone oil containing silicon-hydrogen bonds at the end side;
[0080] (2) Mix and degas the following components in parts by mass:
[0081] 100 parts of phenyl vinyl silicone oil,
[0082] 0.1 to 0.8 parts of catalyst,
[0083] 4 to 8 parts of diluent;
[0084] Then, the mixture is mixed with 400 to 650 parts of a conductive filler and degassed to obtain a B component.
[0085] It should be noted that the present invention can prepare component A and component B through the simple preparation method of the above process, which is easy to use. When in use, component A and component B are mixed in a mass ratio of 1:1, and a low-temperature resistant conductive adhesive with excellent performance can be obtained after medium-temperature curing. The conductive adhesive has excellent low-temperature resistance, can maintain good elasticity to about minus 70°C, is resistant to high and low temperature impact, has excellent conductive performance, and has the characteristics of good bonding. It is suitable for conductive bonding in the fields of target materials, electronics, and military industry.
[0086] The present invention is further described in detail by way of examples below, but the present invention is not limited thereto. In the following examples, unless otherwise specified, the experimental instruments and raw materials involved are all commercially available products.
[0087] Example 1
[0088] The mass fractions of component A are as follows:
[0089]
[0090]
[0091] The mass fractions of component B are as follows:
[0092]
[0093] In this example, the following are used:
[0094] The vinyl content of phenyl vinyl silicone oil is 0.16%, the phenyl content is 2%, and the synthesis method is as follows:
[0095] Take 15g of octaphenylcyclotetrasiloxane D 4Ph, 340g octamethylcyclotetrasiloxane, 10g tetramethyldivinylsiloxane, add 10g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually increase the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer;
[0096] The curing agent is a phenyl hydrogen silicone oil containing a terminal silicon-hydrogen bond, with a terminal silicon-hydrogen bond content of 0.8% and a phenyl content of 2%. The synthesis method is as follows:
[0097] Take 64g of octaphenylcyclotetrasiloxane D 4 Ph, 340g octamethylcyclotetrasiloxane, 60g tetramethylhydrogencyclotetrasiloxane D 4 H, 9g tetramethyldihydrogensiloxane, add 20g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually increase the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer;
[0098] The inhibitor was dibutyl fumarate;
[0099] The diluent is α,ω-dimethyl polydimethylphenylsiloxane with a viscosity of 100 mPa.s and a phenyl content of 5%. The synthesis method is as follows:
[0100] Take 15g of octaphenylcyclotetrasiloxane D 4 Ph, 340g octamethylcyclotetrasiloxane, 30g tetramethylcyclotetrasiloxane, 3g hexamethyldisiloxane, add 10g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually increase the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer;
[0101] The structural formula of the tackifier is as follows:
[0102]
[0103] Among them, a≥4, b≥5, c≥4, d≥3, e≥3;
[0104] The synthesis method of the tackifier is as follows:
[0105] Take 30g of octaphenylcyclotetrasiloxane D 4 Ph, 160g octamethylcyclotetrasiloxane, 22g tetramethylhydrogencyclotetrasiloxane D 4H, 3g hexamethyldisiloxane, add 15g of 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually raise the temperature to 230°C, and stop the reaction when there is no distillate. Take 150g of the transparent polymer in the bottle, place it in a 500ml three-necked flask, add 300ml of toluene solvent, add 3g of 2000ppm chloroplatinic acid isopropanol solution, control the reaction temperature between 30 and 60°C through an oil bath, add 40g of 3-(methacryloyloxy)propyltrimethoxysilane drop by drop, and continue to add 27g of vinyltrimethylsiloxane drop by drop after adding, maintain the above temperature, react for 4h, distill the product after the reaction is completed, remove the low-boiling substances, and obtain the above transparent tackifier. After nuclear magnetic hydrogen spectrum and carbon spectrum tests, it is known that the structure of the prepared tackifier is the above formula.
[0106] The conductive filler is silver-coated copper powder with a particle size of 20 μm;
[0107] The catalyst is chloroplatinic acid.
[0108] The preparation method of the conductive adhesive is as follows:
[0109] a) weighing phenyl vinyl silicone oil, diluent, curing agent, inhibitor and tackifier in parts by mass, adding them into a blender, mixing and degassing at a speed of 1000 r / min and a vacuum degree of -0.9 MPa for 5 min to obtain a mixture;
[0110] b) Weighing a conductive filler by mass and adding it to the above mixture, and then mixing and degassing in a blender at a speed of 1500 r / min and a vacuum degree of -0.9 MPa for 10 min to obtain component A;
[0111] c) weighing phenyl vinyl silicone oil, catalyst, and diluent in parts by mass, adding them into a blender, mixing and degassing at a speed of 1000 r / min and a vacuum degree of -0.9 MPa for 5 min to obtain a mixture;
[0112] d) Weighing a conductive filler by mass and adding it to the above mixture, and then mixing and degassing in a mixer at a speed of 1500 r / min and a vacuum degree of -0.9 MPa for 10 min to obtain component B.
[0113] Example 2
[0114] The mass fractions of component A are as follows:
[0115]
[0116] The mass fractions of component B are as follows:
[0117]
[0118] In this example, the following are used:
[0119] The vinyl content of phenyl vinyl silicone oil is 0.57%, the phenyl content is 8%, and the synthesis method is as follows:
[0120] Take 64g of octaphenylcyclotetrasiloxane D 4 Ph, 240g octamethylcyclotetrasiloxane, 16g tetramethyldivinylsiloxane, add 20g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually increase the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer;
[0121] The curing agent is a phenyl hydrogen silicone oil containing a terminal silicon-hydrogen bond, with a terminal silicon-hydrogen bond content of 0.1% and a phenyl content of 8%. The synthesis method is as follows:
[0122] Take 96g of octaphenylcyclotetrasiloxane D 4 Ph, 200g octamethylcyclotetrasiloxane, 30g tetramethylhydrogencyclotetrasiloxane D 4 H, 6g tetramethyldihydrogensiloxane, add 10g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually increase the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer;
[0123] The inhibitor is acetylene alcohol;
[0124] The diluent is α,ω-dimethyl polydimethylphenylsiloxane with a viscosity of 10mpa.s and a phenyl content of 8%. The synthesis method is as follows:
[0125] Take 64g of octaphenylcyclotetrasiloxane D 4 Ph, 280g octamethylcyclotetrasiloxane, 36g tetramethylcyclotetrasiloxane, 5g hexamethyldisiloxane, add 12g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually increase the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer;
[0126] The tackifier is the same as in Example 1;
[0127] The conductive filler is silver-coated aluminum powder with a particle size of 20 μm;
[0128] The catalyst is the same as in Example 1.
[0129] The preparation method of the conductive adhesive is the same as that of Example 1.
[0130] Example 3
[0131] The mass fractions of component A are as follows:
[0132]
[0133] The mass fractions of component B are as follows:
[0134]
[0135] In this example, the following are used:
[0136] The vinyl content of phenyl vinyl silicone oil is 0.53%, the phenyl content is 6%, and the synthesis method is as follows:
[0137] Take 52g of octaphenylcyclotetrasiloxane D 4 Ph, 340g octamethylcyclotetrasiloxane, 15g tetramethyldivinylsiloxane, add 10g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually increase the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer;
[0138] The curing agent is a phenyl hydrogen silicone oil containing a terminal silicon-hydrogen bond, with a terminal silicon-hydrogen bond content of 0.5% and a phenyl content of 6%. The synthesis method is as follows:
[0139] Take 85g of octaphenylcyclotetrasiloxane D 4 Ph, 230g octamethylcyclotetrasiloxane, 45g tetramethylhydrogencyclotetrasiloxane D 4 H, 3g tetramethyldihydrogensiloxane, add 18g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually increase the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer;
[0140] The inhibitor was tetramethyltetravinylcyclotetrasiloxane, purchased from Shenzhen Jipeng Silicon Fluoride Materials Co., Ltd., with the brand name VM-20;
[0141] The diluent is α,ω-dimethyl polydimethylphenylsiloxane with a viscosity of 50mpa.s and a phenyl content of 5%. The synthesis method is as follows:
[0142] Take 18g of octaphenylcyclotetrasiloxane D 4 Ph, 330g octamethylcyclotetrasiloxane, 50g tetramethylcyclotetrasiloxane, 9g hexamethyldisiloxane, add 20g 98% concentrated sulfuric acid, control the reaction temperature at 30-50°C, react for 24h, distill under reduced pressure and gradually increase the temperature to 230°C, stop the reaction when there is no distillate, and obtain a transparent polymer;
[0143] The tackifier is the same as in Example 1;
[0144] The conductive filler is a mixture of silver-coated aluminum powder with a particle size of 40 μm and silver-coated copper powder with a particle size of 40 μm in a mass ratio of 1:1;
[0145] The catalyst is the same as in Example 1.
[0146] The preparation method of the conductive adhesive is the same as that of Example 1.
[0147] Comparative Example 1
[0148] The conductive adhesive was prepared according to the formula and method of Example 1, except that:
[0149] The tackifier was replaced with the same amount of the following structural tackifier:
[0150]
[0151] Wherein, x≥8, y≥5, and z≥4; the preparation method of the tackifier is as follows:
[0152] Take 24g of tetramethylhydrogencyclotetrasiloxane D 4 H, 16.3g of vinyltrimethoxysilane and 13.7g of allyl glycidyl ether were placed in a 250ml three-necked flask, 30mL of toluene was added as a solvent, and the reaction was carried out under nitrogen protection at a reaction temperature of 80°C and a reaction time of 4 hours; after the reaction was completed, the product was distilled and low-boiling substances were removed to obtain a transparent tackifier.
[0153] Test Case
[0154] In order to investigate the mechanical properties and conductive bonding of the conductive adhesives prepared in the aforementioned embodiments and comparative examples, component A and component B in the aforementioned embodiments and comparative examples were mixed at a mass ratio of 1:1, and then vacuumed to remove bubbles. The conductive adhesive was then cured in an oven at 80°C for 2h to prepare a 2mm thick test piece, and a tensile performance test was performed. A bonding test was also performed according to the shear standard. The curing conditions were the same as above. The relevant test results are shown in Table 1 below.
[0155] Among them, the volume resistivity is tested according to GJB 548B-2005;
[0156] Hardness is tested according to GB / T 531.1-2008;
[0157] The tensile strength is tested according to GB / T 528-2009;
[0158] Elongation at break is tested according to GB / T 528-2009;
[0159] Shear strength / aluminum-aluminum is tested according to GB / T 7124-2008;
[0160] Density is tested according to GB / T 13477.2-2002;
[0161] The low-temperature hardening temperature is measured by DSC (differential scanning calorimetry).
[0162] Table 1. Physical properties test results:
[0163] Example Example 1 Example 2 Example 3 Comparative Example 1 Volume resistivity (Ω·cm) <![CDATA[1.1×10 -4 ]]> <![CDATA[8×10 -3 ]]> <![CDATA[2×10 -3 ]]> <![CDATA[6×10 -4 ]]> Hardness(Shore A) 65 50 58 62 Tensile strength(MPa) 2.4 1.8 2 2.2 Elongation at break (100%) 45 60 62 30 Shear strength / aluminum-aluminum (Mpa) 1.5 1.8 2.1 1.4 <![CDATA[Density (g / cm -3 )]]> 2.8 2.6 2.68 2.8 Low temperature hardening temperature℃ -70 -71 -70 -70
[0164] From the results in Table 1, it can be seen that the conductive adhesive of the present invention has good low temperature resistance. Ordinary potting adhesives will harden and lose rubber elasticity at temperatures between -50°C and -55°C, while the conductive adhesive of the present invention can maintain elasticity to about -70°C. The elastic conductive adhesive solves the problem of easy cracking when tin welding is used for bonding brittle target materials. Compared with the conductive potting adhesive of the same type of addition-type silicone with bonding properties, the test piece of the conductive adhesive of the present invention after being cured at 80°C can have good tensile strength, elongation at break, shear strength, etc., and does not need to be heated to a high temperature of more than 100°C, and can achieve medium-temperature curing and bonding, while having excellent conductive properties.
[0165] Compared with Examples 2 and 3, the amount of conductive filler used in Example 1 and Comparative Example 1 is large, so the volume resistivity of the conductive adhesive of Example 1 and Comparative Example 1 is smaller and has better conductive performance. The formula of Example 1 and Comparative Example 1 is the same. Compared with Example 1, the conductive adhesive of Comparative Example 1 uses a different tackifier, and the volume resistivity of Comparative Example 1 is increased by about 5 times, and the conductivity is greatly reduced; compared with Example 1, the tensile strength, elongation at break and other properties of the conductive adhesive of Comparative Example 1 are also reduced. It can be seen that the conductive adhesive in the embodiment of the present invention uses the aforementioned specific structure of the tackifier, and the conductive performance of the conductive adhesive is greatly improved, while the tensile strength, elongation at break and other properties are also improved, and the comprehensive performance of the conductive adhesive is more excellent.
[0166] In the description of the present application, it should be noted that the terms "upper", "lower", "inside", "outside", "front", "back", "left", "right", etc. indicate directions or positional relationships based on the directions or positional relationships in the working state of the present application. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limitations on the present application.
[0167] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "install", "connect" and "connect" should be understood in a broad sense. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0168] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. A conductive adhesive for a target material, characterized in that: The conductive glue for target material comprises component A and component B; wherein, In parts by mass, component A comprises: In parts by mass, component B comprises: Wherein, the curing agent is selected from phenyl hydrogen-containing silicone oil containing silicon-hydrogen bonds at the terminal side.
2. The conductive adhesive for target material according to claim 1, characterized in that: The structure of the tackifier is as follows: Among them, a≥4, b≥5, c≥4, d≥3, e≥3.
3. The conductive adhesive for target material according to claim 1, characterized in that: The phenyl vinyl silicone oil is one or more selected from phenyl vinyl silicone oils having a vinyl content of 0.16 to 0.57% and a phenyl content of 2 to 8%.
4. The conductive adhesive for target material according to claim 1, characterized in that: The curing agent is one or more selected from phenyl hydrogen-containing silicone oils having a terminal silicon-hydrogen bond content of 0.1 to 0.8% and a phenyl content of 2 to 8%.
5. The conductive adhesive for target material according to claim 1, characterized in that: The inhibitor is one or more selected from acetylenic alcohols, ether compounds, amine compounds, vinyl ring compounds, and fumarate compounds.
6. The conductive adhesive for target material according to claim 1, characterized in that: The diluent is selected from α,ω-dimethyl polydimethylphenylsiloxane with a viscosity of 10 to 100 mPa.s and a phenyl content of 2 to 8%.
7. The conductive adhesive for target material according to claim 1, characterized in that: The conductive filler is one or more spherical silver-coated copper powders and / or silver-coated aluminum powders with different particle sizes.
8. The conductive adhesive for target material according to claim 7, characterized in that: The particle size of the conductive filler is 20 to 50 μm.
9. The conductive adhesive for target material according to claim 1, characterized in that: The catalyst is a platinum catalyst.
10. A method for preparing a conductive adhesive for a target material, characterized in that: include: (1) Mix the following components by weight and degas: Then, it is mixed with 400 to 650 parts of conductive filler and degassed to obtain component A; Wherein, the curing agent is selected from phenyl hydrogen-containing silicone oil containing silicon-hydrogen bonds at the end side; (2) Mix and degas the following components in parts by mass: 100 parts of phenyl vinyl silicone oil, 0.1 to 0.8 parts of catalyst, 4 to 8 parts of diluent; Then, the mixture is mixed with 400 to 650 parts of a conductive filler and degassed to obtain a B component.